2020
DOI: 10.1007/s12035-020-02044-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aquaporin 4 Decreases Amyloid Aβ40 Drainage Around Cerebral Vessels

Abstract: Aquaporin-4 (AQP4) is located mainly in the astrocytic end-feet around cerebral blood vessels and regulates ion and water homeostasis in the brain. While deletion of AQP4 is shown to reduce amyloid-β (Aβ) clearance and exacerbate Aβ peptide accumulation in plaques and vessels of Alzheimer’s disease mouse models, the mechanism and clearing pathways involved are debated. Here, we investigated how inhibiting the function of AQP4 in healthy male C57BL/6 J mice impacts clearance of Aβ40, the more soluble Aβ isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 71 publications
(86 reference statements)
1
26
0
Order By: Relevance
“…Doxycycline induced adipocyte specific NaKtide expression in these WD fed mice significantly attenuated the Iba1-positive microglia in the hippocampus ( Figure S3 ). These findings were consistent with the plasma levels of amyloid beta-40 (Aβ-40), a marker of cognitive decline ( Jakel et al., 2020 ; Rosu et al., 2020 ; Tsai et al., 2021 ; Watt et al., 2020 ), which showed significant increases in the WD fed mice ( Figure 3 F). The increase in Aβ-40 levels was significantly attenuated by doxycycline induced NaKtide expression ( Figure 3 F).…”
Section: Resultssupporting
confidence: 82%
“…Doxycycline induced adipocyte specific NaKtide expression in these WD fed mice significantly attenuated the Iba1-positive microglia in the hippocampus ( Figure S3 ). These findings were consistent with the plasma levels of amyloid beta-40 (Aβ-40), a marker of cognitive decline ( Jakel et al., 2020 ; Rosu et al., 2020 ; Tsai et al., 2021 ; Watt et al., 2020 ), which showed significant increases in the WD fed mice ( Figure 3 F). The increase in Aβ-40 levels was significantly attenuated by doxycycline induced NaKtide expression ( Figure 3 F).…”
Section: Resultssupporting
confidence: 82%
“…Additionally, AQP4 deficiency downregulates the expression of low-density lipoprotein receptor-related protein-1 (LRP1), which mediates Aβ excretion [ 20 - 23 ]. In a recent study that used two-photon in vivo imaging to visualize vessels using sulforhodamine 101 (SR101), significantly more perivascular Aβ deposition was observed in mice treated with the AQP4 inhibitor TGN-020 than in mice in the control group [ 24 ]. This is direct evidence that the inhibition of AQP4 function can reduce Aβ vascular drainage.…”
Section: Aqp4 and Alzheimer’s Diseasementioning
confidence: 99%
“…Our data point to the possible involvement of BMPs in conditions where a mislocalization of AQP4 is paired with its preserved or enhanced expression. Alzheimer’s Disease (AD) is a notable example: a decade ago it was shown in a mouse model of AD that AQP4 was conspicuously absent from endfeet adjoining amyloid plaques ( Yang et al, 2011 ), while more recent studies have demonstrated reduced amyloid clearance following targeted disruption of Aqp4 ( Iliff et al, 2012 ; Xu et al, 2015 ; Smith et al, 2019 ; Rosu et al, 2020 ). AD is associated with upregulation of BMPs and activation of the Smad1/5/9 pathway ( Li et al, 2008 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%